Stability of West Nile Virus (Flaviviridae: Flavivirus) RNA in Mosquito Excreta. Issue 4 (2nd April 2019) - Ramírez, Ana L; Hall-Mendelin, Sonja; Hewitson, Glen R; McMahon, Jamie L; Staunton, Kyran M; Ritchie, Scott A; van den Hurk, Andrew F
Abstract: Arbovirus surveillance is crucial for the implementation of vector-borne disease control measures. Recently, it has been demonstrated that mosquitoes with a disseminated arbovirus infection excrete viral RNA, which can be detected by molecular methods. Thereby, mosquito excreta has been proposed as a sample type that could be utilized for arbovirus surveillance. In this study, we evaluated if West Nile virus (Kunjin strain, WNVKUN ) RNA in Culex annulirostris Skuse (Diptera: Culicidae) excreta deposited on different substrates could be detected after storage for up to 2 wk at tropical conditions of high heat and humidity. No significant drop in relative quantity of WNVKUN RNA (determined by comparison of C t values) in excreta deposited on Flinders Associate Technologies (FTA) cards was observed over 14 d, suggesting that RNA was stable for that time. There was no significant difference in relative quantity of WNVKUN RNA in excreta deposited on FTA cards or polycarbonate substrates after 24 h. However, after 7 and 14 d, there was a significant decline in the relative quantity of viral RNA in the excreta stored on polycarbonate substrates. For incorporation in arbovirus surveillance programs, we recommend the use of polycarbonate substrates for excreta collection in mosquito traps deployed overnight, and the integration of FTA cards in traps serviced weekly or fortnightly. Polycarbonate substrates facilitate the collection of the majority of excreta from a trap, and while FTA cards offer limited area coverage, they enable preservation of viral RNA in tropical conditions for extended periods of time.